Composite reinforced PP decorative film and preparation process thereof

By adding short glass fiber and polyguaerosol to the PP decorative film, and preparing reinforcement agents to optimize process conditions, the problem of insufficient mechanical properties of the existing PP decorative film is solved, which significantly improves its in high temperature and light. Weather resistance and stability.

CN119119540AInactive Publication Date: 2024-12-13ZHEJIANG JINSHENG DEOCRATION MATERIAL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411629180.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The mechanical properties of the existing PP decorative films still need to be further improved, especially in high temperature and light conditions, the weather resistance and stability are insufficient, and antioxidants are easy to decompose, resulting in a decrease in mechanical properties.

Method used

By mixing PP, nucleating agent, short glass fiber, antioxidant, light stabilizer, toughening agent, and reinforcement agent to prepare a composite reinforced PP decorative film, controlling the moisture content and diameter of the short glass fiber, and preparing Juyuchuang Lycium is used as an antioxidant and reinforcement is prepared by ball milling, which optimizes the stirring and granulation conditions to form an effective enhancement network and synergistic effect to improve the mechanical properties of the material.

Benefits of technology

The tensile strength, notch impact strength and elongation of break of composite reinforced PP decorative film are significantly improved, the mechanical properties and stability of the material are enhanced, and excellent performance can be maintained under high temperature and light conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119540A_ABST
    Figure CN119119540A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of chemical products, in particular to a composite reinforced PP decorative film and a preparation process thereof. The problem that the mechanical property of the PP decorative film is poor is solved. The composite reinforced PP decorative film is prepared by mixing PP, a nucleating agent, short glass fibers, an antioxidant, a light stabilizer, a flexibilizer and a reinforcing agent. The water content, the diameter and the dosage of the short glass fiber and the dosage of the nucleating agent are controlled; controlling the molar ratio of lauryl sodium sulfate to guaiacol, the concentration of the hydrogen peroxide aqueous solution and the stirring time; controlling the type of inorganic salt, the mass ratio of sodium lignin sulfonate to dolomite, the ball-milling rotating speed and the ball-milling particle size; controlling the temperature, stirring time and stirring speed of the mixture I and the mixture II and the vacuum degree of the mixture I; the granulation temperature, the vacuum degree, the calendering time and the calendering film thickness are controlled, and the prepared composite reinforced PP decorative film has excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical products, in particular to a composite reinforced PP decorative film and a preparation process thereof. Background Art

[0002] With the rapid economic development and the continuous improvement of material living standards, my country's furniture industry and interior decoration industry have shown a rapid growth trend in recent years. Decorative films have been widely used in all walks of life. Decorative films can save a lot of wood instead of wood grain paper and achieve the purpose of environmental protection. The decorative films currently used in the market are made of various materials, such as PVC film, PP film, PET film, etc. PP is a light-density thermoplastic plastic with a high limit use temperature, can be recycled, and has a low price. Decorative films made of PP materials have the advantages of light weight, low cost, and good processing performance. They are widely used in the decoration of furniture, cabinets, wood, floors, and walls. Its visual effect is comparable to that of wood veneer. In addition, PP films are degradable when recycled, and only release water and carbon dioxide when burned, without producing any toxic gases, making a huge contribution to environmental protection.

[0003] Chinese patent CN116041844A discloses a yellowing-resistant PP decorative film, comprising the following raw materials in parts by weight: 110-130 parts of polypropylene, 20-30 parts of acrylate modifier, 10-20 parts of silazane polymer, 5-10 parts of methyl methacrylate, 5-10 parts of diisooctyl sebacate, 0.3-0.5 parts of ultraviolet absorber and 0.3-0.5 parts of antioxidant. The invention adds acrylate modifier and silazane polymer to play a good masking role on the PP decorative film, improves the mechanical properties of the modified PP decorative film by adding methyl methacrylate and diisooctyl sebacate, and uses ultraviolet absorber and antioxidant together to have a significant synergistic effect, which can improve the thermal stability of the PP decorative film. The yellowing-resistant PP decorative film thus prepared has excellent yellowing resistance, thereby greatly improving the sunscreen effect and service life of the PP decorative film. However, the antioxidant used in the invention will decompose or become ineffective if exposed to high temperature, light or humidity for a long time. In addition, when the ultraviolet absorber and the antioxidant are mixed, the temperature is too high, which can easily lead to the decomposition of the two at high temperature, thereby reducing the mechanical properties of the PP decorative film at high temperature.

[0004] Chinese patent CN115838512A discloses a composite reinforced PP decorative film and its preparation method. In the invention, the composite reinforced PP decorative film is composed of the following components: 80-100 parts of PP, 10-25 parts of modifier, 5-10 parts of compatibilizer, 0.1-1.5 parts of antioxidant A, 0.1-0.5 parts of antioxidant B, 0.1-0.5 parts of dispersant, 5-15 parts of toughening agent, and 0.1-0.5 parts of lubricant. The synergistic effect between the components improves the weather resistance and acid and alkali resistance of the PP decorative film, can effectively prevent the thermal oxidation degradation of the polymer material during long-term aging, can improve the discoloration resistance of the polymer material under high temperature processing conditions, and improve the physical properties of the PP decorative film. However, the low molecular weight hindered phenol antioxidant in the invention is easy to volatilize during the polymer processing process, and is easy to separate from the polymer during long-term use, resulting in a decrease in the mechanical properties of the PP decorative film.

[0005] Although the PP decorative film prepared in the prior art has made certain progress, it still has some shortcomings and its mechanical properties still need to be further improved.

[0006] Therefore, a composite reinforced PP decorative film and its preparation process are proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a composite reinforced PP decorative film and a preparation process thereof, wherein the composite reinforced PP decorative film is prepared by mixing PP, a nucleating agent, short glass fibers, an antioxidant, a light stabilizer, a toughening agent, and a reinforcing agent. By controlling the water content of the short glass fibers, the diameter of the short glass fibers, the amount of the nucleating agent, and the amount of the short glass fibers, the stability and strength of the short glass fibers can be maintained, an effective reinforcing network can be formed, and the mechanical properties of the PP decorative film can be improved; by preparing polyguaiacol as an antioxidant, controlling the molar ratio of sodium dodecyl sulfate and guaiacol, the concentration of the hydrogen peroxide aqueous solution, and the stirring time, the obtained antioxidant has good stability and strong antioxidant properties, and applying it to the PP decorative film and changing the amount of the antioxidant can protect the molecular chains of the PP material from being destroyed by external forces, thereby improving the mechanical properties of the PP decorative film; by preparing the reinforcing agent, controlling the type of inorganic salt By controlling the mass ratio of mixture one, sodium lignin sulfonate and dolomite, the ball milling speed and the ball milling particle size, the synergistic effect of each component can be fully exerted, the mechanical properties and application effect of the reinforcing agent can be improved, thereby improving the mechanical properties of the PP decorative film; by respectively controlling the temperature, stirring time, stirring speed of mixture one and mixture two and the vacuum degree of mixture one, it is helpful to fully mix the substances and reduce the agglomeration phenomenon, improve the uniformity and consistency of the material, thereby enhancing the overall mechanical properties; by controlling the granulation temperature, vacuum degree, calendering time and calendering film thickness, the material can be fully extended, the film thickness is uniform, it can withstand sufficient impact strength, and the mechanical properties are improved.

[0008] To achieve the above object, the present invention provides the following technical solutions: In one aspect, the present invention provides a process for preparing a composite reinforced PP decorative film, wherein the composite reinforced PP decorative film is prepared by the following steps: Sodium dodecyl sulfate and guaiacol are dissolved in a phosphate buffer at a molar ratio of 1:5-10 to obtain a mixed solution 1; horseradish peroxidase solution is dripped into the mixed solution 1 at room temperature to obtain a mixed solution 2; 10-15wt% aqueous hydrogen peroxide solution is added to the mixed solution 2, and the mixture is stirred for 1.5-2h, centrifuged, and filtered to obtain a filter cake; the filter cake is washed with deionized water and dried to obtain polyguaiacol as an antioxidant; Add inorganic salt, sodium lignin sulfonate, dolomite and the deionized water into a ball mill steel tank, mix them evenly, and then ball mill them at a speed of 200-300 r / min to obtain a reinforcing agent; 70 parts of PP, 0.5-1.5 parts of nucleating agent and 5-10 parts of short glass fiber are added to a reactor, stirred for 1-2 hours at a temperature of 170-180°C and a vacuum degree of 0.1-0.5MPa to obtain a mixture one; the stirring speed is 180-250r / min; 2-4 parts of the antioxidant, 2 parts of the light stabilizer, 2-5 parts of the toughening agent, and 8-12 parts of the reinforcing agent are added to the mixture one, mixed evenly at 90-100°C, and stirred for 1-2 hours to obtain a mixture two; the stirring speed is 150-200r / min; the mixture two is added to a twin-screw extruder, extruded and granulated at a temperature of 180-220°C and a vacuum degree of 0.06-0.12MPa to obtain a masterbatch; the masterbatch is added to a four-roll calender and calendered into a film at 190-250°C, and the film is cooled and rolled to obtain the composite reinforced PP decorative film.

[0009] Preferably, the preparation steps of the antioxidant are as follows: dissolving the sodium dodecyl sulfate and the guaiacol in the phosphate buffer to obtain the mixed solution one; dissolving the horseradish peroxidase in the phosphate buffer to obtain the horseradish peroxidase solution; dripping the horseradish peroxidase solution into the mixed solution one at room temperature to obtain the mixed solution two; adding the hydrogen peroxide aqueous solution to the mixed solution two, reacting for 20 minutes, adding the remaining hydrogen peroxide aqueous solution, stirring for 1.5-2 hours, centrifuging, and filtering to obtain the filter cake; washing the filter cake three times with the deionized water, and vacuum drying to obtain the polyguaiacol as the antioxidant; the concentration of the phosphate buffer is 0.15M.

[0010] Preferably, the inorganic salt is one of magnesium sulfate, magnesium oxalate, potassium chloride and calcium chloride.

[0011] Preferably, the ball-milled particle size is 4-8 μm.

[0012] Preferably, the nucleating agent is WBG-Ⅱ; the toughening agent is ABS; and the light stabilizer is AM-101.

[0013] Preferably, the film thickness is 0.15-0.35 mm.

[0014] Preferably, the mass ratio of the sodium lignin sulfonate to the dolomite is 1:1-4.

[0015] Preferably, the moisture content of the short glass fibers is 0.05%-0.15%.

[0016] Preferably, the short glass fibers have a diameter of 9-13 μm.

[0017] Another aspect of the present invention provides a composite reinforced PP decorative film, wherein the raw materials for producing the composite reinforced PP decorative film include PP, a nucleating agent, short glass fibers, an antioxidant, a light stabilizer, a toughening agent, and a reinforcing agent; the composite reinforced PP decorative film is prepared by any one of the preparation processes described above; by controlling the water content of the short glass fibers, the diameter of the short glass fibers, the amount of the nucleating agent, and the amount of the short glass fibers, the composite reinforced PP decorative film has a tensile strength of 46 MPa, a notched impact strength of 10.5 MPa, and an elongation at break of 328%; by preparing polyguaiacol as an antioxidant, controlling the molar ratio of sodium dodecyl sulfate and guaiacol, the concentration of the hydrogen peroxide aqueous solution, and the stirring time, the composite reinforced PP decorative film has a tensile strength of 46 MPa, a notched impact strength of 10.5 MPa, and an elongation at break of 328%. The tensile strength of the decorative film is 59MPa, and the right-angle tear strength is 187N / mm; by preparing a reinforcing agent, controlling the type of inorganic salt, the mass ratio of sodium lignin sulfonate and dolomite, the ball milling speed, and the ball milling particle size, the obtained composite reinforced PP decorative film has a tensile strength of 68MPa and a right-angle tear strength of 199N / mm; by respectively controlling the temperature, stirring time, stirring speed of mixture one and mixture two and the vacuum degree of mixture one, the obtained composite reinforced PP decorative film has a tensile strength of 87MPa and a notched impact strength of 14.6MPa; by controlling the granulation temperature, vacuum degree, calendering time, and calendered film thickness, the obtained composite reinforced PP decorative film has a notched impact strength of 16.2MPa and an elongation at break of 360%.

[0018] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention can increase the bonding area between the fiber and the matrix and maintain the stability and strength of the short glass fiber by controlling the moisture content and diameter of the short glass fiber, thereby ensuring that the PP decorative film has excellent mechanical properties; by controlling the amount of the nucleating agent and the amount of the short glass fiber, an effective reinforcement network can be formed, and the prepared composite reinforced PP decorative film has a tensile strength of 46 MPa, a notched impact strength of 10.5 MPa, and an elongation at break of 328%, showing significantly improved mechanical strength.

[0019] 2. The present invention prepares polyguaiacol as an antioxidant, controls the molar ratio of SDS to guaiacol, the concentration of the hydrogen peroxide solution, and the stirring time, and the obtained antioxidant has good stability. The antioxidant is applied to the PP decorative film and the amount of the antioxidant is changed to protect the molecular chain of the PP material from being destroyed by external forces, prevent the molecular chain from being broken and degraded, thereby maintaining the stability of the mechanical properties of the PP decorative film. The prepared composite reinforced PP decorative film has a tensile strength of 59 MPa and a right-angle tear strength of 187 N / mm.

[0020] 3. The present invention prepares the reinforcing agent, controls the type of inorganic salt, the mass ratio of sodium lignin sulfonate and dolomite, the ball milling speed, and the ball milling particle size, so as to give full play to the synergistic effect of each component, improve the mechanical properties and application effects of the reinforcing agent, and improve the anti-destruction ability of the PP decorative film. It can also make the reinforcing agent more effectively fill the gaps in the matrix, reduce defects, and improve the overall mechanical properties of the PP decorative film. The prepared composite reinforced PP decorative film has a tensile strength of 68MPa and a right-angle tear strength of 199N / mm.

[0021] 4. The present invention controls the temperature of mixture one, which is conducive to the uniform dispersion of short glass fibers in the PP matrix, promotes the function of the nucleating agent, and promotes the crystallization of PP, thereby enhancing the tensile strength and notched impact strength of the PP decorative film; controls the vacuum degree, helps to remove bubbles and volatile substances in the mixture, and improves the density of the material; controls the stirring time and stirring speed of mixture one, which helps to promote the full mixing of PP and short glass fibers, reduce agglomeration, and improve the uniformity and consistency of the material, thereby enhancing the overall mechanical properties; controls the temperature, stirring time, and stirring speed of mixture two, which helps to uniformly distribute the functional additives in the mixture, and the tensile strength and notched impact strength of the material are significantly improved. The prepared composite reinforced PP decorative film has a tensile strength of 87 MPa and a notched impact strength of 14.6 MPa.

[0022] 5. The present invention controls the granulation temperature and vacuum degree so that the material is fully melted during the granulation extrusion process without residual bubbles, thereby improving the mechanical properties of the PP decorative film; by controlling the calendering time and the thickness of the calendered film, the material is fully extended and the film thickness is uniform, which can withstand sufficient impact strength. The prepared composite reinforced PP decorative film has a notched impact strength of 16.2 MPa and an elongation at break of 360%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a graph showing the mechanical properties test results of the composite reinforced PP decorative films of Examples 59, 62-72 of the present invention. DETAILED DESCRIPTION

[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] See also Figure 1 The present invention provides a composite reinforced PP decorative film and a preparation process thereof, and the technical scheme is as follows: The substance information involved in the present invention is as follows: Sodium dodecyl sulfate (SDS) CAS: 151-21-3; guaiacol CAS: 90-05-1; hydrogen peroxide CAS: 7722-84-1; magnesium sulfate CAS: 7487-88-9; magnesium oxalate CAS: 6150-88-5; potassium chloride CAS: 7447-40-7; calcium chloride CAS: 10043-52-4; sodium lignin sulfonate CAS: 8061-51-6; dolomite CAS: 16389-88-1; PP CAS: 9003-07-0; AM-101 CAS: 20649-88-1; ABS CAS: 9003-56-9; horseradish peroxidase was purchased from Shanghai Bioengineering Co., Ltd.; WBG-II was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; short glass fiber was purchased from Changchun Artificial Resin Factory Co., Ltd.

[0026] Example 1 The SDS and the guaiacol are dissolved in 45 ml of the phosphate buffer at a molar ratio of 1:5 to obtain the mixed solution 1; 0.1 mmol of the horseradish peroxidase is dissolved in 5 ml of the phosphate buffer to obtain the horseradish peroxidase solution; the horseradish peroxidase solution is dripped into the mixed solution 1 at room temperature to obtain the mixed solution 2; 1 ml of the hydrogen peroxide aqueous solution is added to the mixed solution 2, and after reacting for 20 minutes, the remaining 2 ml of the hydrogen peroxide aqueous solution is added, and the mixture is stirred for 1.5 hours, centrifuged, and filtered to obtain a filter cake; the filter cake is washed three times with the deionized water, and vacuum dried to obtain the antioxidant; the concentration of the phosphate buffer is 0.15 M; the concentration of the hydrogen peroxide aqueous solution is 10 wt %; the total amount of SDS and guaiacol added is 7 mmol; Inorganic salt magnesium sulfate, sodium lignin sulfonate, dolomite, and the deionized water are added to a ball mill steel tank and mixed evenly, and then ball milled at a speed of 200 r / min to obtain a reinforcing agent; the mass ratio of the sodium lignin sulfonate to the dolomite is 1:1; the ball milled particle size is 4 μm; 70 parts of PP, 0.5 parts of nucleating agent and 5 parts of short glass fiber are added to a reactor, and stirred for 1 hour at a temperature of 170°C and a vacuum degree of 0.1MPa to obtain a mixture one; the stirring speed is 180r / min; 2 parts of the antioxidant polyguaiacol, 2 parts of the light stabilizer AM-101, 2 parts of the toughening agent ABS, and 8 parts of the reinforcing agent are added to the mixture one, mixed evenly at 90°C, and stirred for 1 hour to obtain a mixture two; the stirring speed is 150r / min; the mixture two is added to a twin-screw extruder, extruded and granulated at a temperature of 180°C and a vacuum degree of 0.06MPa to obtain a masterbatch; the masterbatch is added to a four-roll calender and calendered into a film at 190°C, and the film is cooled and rolled to obtain the composite reinforced PP decorative film; the water content of the short glass fiber is 0.05%; the diameter of the short glass fiber is 9μm; the thickness of the film is 0.15mm.

[0027] Example 2-14 Referring to the preparation method and parameter conditions of Example 1, the specific differences are shown in Table 1.

[0028] Table 1 Specific preparation parameters of Examples 2-14

[0029] Comparative Example 1 A composite reinforced PP decorative film was prepared according to the method of Example 1, except that short glass fibers were not added.

[0030] Comparative Example 2 A composite reinforced PP decorative film was prepared according to the method of Example 1, except that no nucleating agent was added.

[0031] Example 15 Mechanical properties test Tensile strength test: The sample size is 12cm×4cm×0.4cm. The test is carried out according to GB / T1040.1-2018 standard. The tensile properties are tested by a universal material testing machine with a tensile rate of 50mm / min.

[0032] Notched impact strength test: Tested in accordance with GB / T1043.1-2008 standard, measuring injection molded samples at 23°C.

[0033] Elongation at break test: The elongation at break of the material was tested according to ISO 527, with a test speed of 50 mm / min. The results are shown in Table 2.

[0034] Table 2 Mechanical properties test of Examples 1-14 and Comparative Examples 1-2

[0035] The diameter of the glass fiber determines the size of its specific surface area and also has a certain influence on the strength of the fiber itself. It can be seen from Table 2 that in Examples 1-4, due to the structural inhomogeneity of the glass fiber, microcracks and microdefects exist on its surface and inside. As the diameter of the glass fiber increases, the cracks and defects increase. The fiber is easy to break under the action of external force, and the specific surface area of ​​the fiber decreases, resulting in a decrease in the bonding area between the fiber and the matrix. The mechanical properties of the prepared PP decorative film gradually decrease. In Example 1, the best effect is achieved when the short glass fiber diameter is 9μm. The short glass fiber contains alkali metals, and the water content has a great influence on its strength. Under the action of water, Na +Migration to the surface turns into alkaline to erode the short glass fibers, which will reduce the strength of the fibers. In Examples 1, 5-8, the short glass fibers have too high a water content, which will lead to a decrease in the mechanical properties of the material during processing; in Example 5, when the water content of the short glass fibers is 0.07%, the stability and strength of the short glass fibers can be maintained, thereby ensuring that the PP decorative film has excellent mechanical properties. In Examples 5, 9-10, the short glass fiber content is too high, which will lead to enhanced interactions between the fibers, forming agglomeration or entanglement, which will not only reduce the dispersion of the fibers, but may also cause stress concentration, resulting in a decrease in the mechanical properties of the PP decorative film. In addition, too much short glass fiber will increase the brittleness of the material and reduce its toughness; and when the short glass fiber content is too low, the mechanical properties of the material cannot be significantly improved. In Example 9, when the amount of short glass fibers is 8 parts, they can be evenly dispersed in PP to form an effective reinforcement network, thereby enhancing the mechanical properties of the PP decorative film. In Examples 9, 11-14, when the amount of nucleating agent is too much, excessive crystallization behavior will be triggered, resulting in excessive grain boundaries and defects inside the material, which will become stress concentration points, thereby reducing the mechanical properties of the material. In Example 12, when the short glass fiber diameter is 9 μm, the water content of the short glass fiber is 0.07%, the amount of short glass fiber is 8 parts, and the amount of nucleating agent is 1 part, it can synergize with the short glass fiber, and the mechanical properties of the composite reinforced PP decorative film prepared are the best, with a tensile strength of 46 MPa, a notched impact strength of 10.5 MPa, and an elongation at break of 328%. In Comparative Example 1, short glass fibers were not added to the PP decorative film, and the tensile strength of the PP decorative film was reduced to 25 MPa, the notched impact strength was reduced to 4.1 MPa, and the elongation at break was reduced to 290%; in Comparative Example 2, no nucleating agent was added to the PP decorative film, and the tensile strength of the PP decorative film was reduced to 21 MPa, the notched impact strength was reduced to 4.3 MPa, and the elongation at break was reduced to 282%.

[0036] Example 16

[0037] The SDS and the guaiacol are dissolved in 45 ml of the phosphate buffer at a molar ratio of 1:6 to obtain the mixed solution 1; 0.1 mmol of the horseradish peroxidase is dissolved in 5 ml of the phosphate buffer to obtain the horseradish peroxidase solution; the horseradish peroxidase solution is dripped into the mixed solution 1 at room temperature to obtain the mixed solution 2; 1 ml of the hydrogen peroxide aqueous solution is added to the mixed solution 2, and after reacting for 20 minutes, the remaining 2 ml of the hydrogen peroxide aqueous solution is added, and the mixture is stirred for 1.5 hours, centrifuged, and filtered to obtain a filter cake; the filter cake is washed three times with the deionized water, and vacuum dried to obtain the antioxidant; the concentration of the phosphate buffer is 0.15 M; the concentration of the hydrogen peroxide aqueous solution is 10 wt%; the total amount of SDS and guaiacol added is 7 mmol Inorganic salt magnesium sulfate, sodium lignin sulfonate, dolomite, and the deionized water are added to a ball mill steel tank and mixed evenly, and then ball milled at a speed of 200 r / min to obtain a reinforcing agent; the mass ratio of the sodium lignin sulfonate to the dolomite is 1:1; the ball milled particle size is 4 μm; 70 parts of PP, 1 part of nucleating agent and 8 parts of short glass fibers are added to a reactor, and stirred for 1 hour at a temperature of 170°C and a vacuum degree of 0.1 MPa to obtain a mixture one; the stirring speed is 180 r / min; 2 parts of the antioxidant polyguaiacol, 2 parts of the light stabilizer AM-101, 2 parts of the toughening agent ABS, and 8 parts of the reinforcing agent are added to the mixture one, mixed evenly at 90°C, and stirred for 1 hour to obtain a mixture two; the stirring speed is 150 r / min; the mixture two is added to a twin-screw extruder, extruded and granulated at a temperature of 180°C and a vacuum degree of 0.06 MPa to obtain a masterbatch; the masterbatch is added to a four-roll calender and calendered into a film at 190°C, and the film is cooled and rolled to obtain the composite reinforced PP decorative film; the water content of the short glass fiber is 0.07%; the diameter of the short glass fiber is 9 μm; the thickness of the film is 0.15 mm.

[0038] Examples 17-27 Referring to the preparation method and parameter conditions of Example 1, the specific differences are shown in Table 3.

[0039] Table 3 Specific preparation parameters of Examples 17-27

[0040] Comparative Example 3 A composite reinforced PP decorative film was prepared according to the method of Example 1, except that no antioxidant was added.

[0041] Example 28 Mechanical properties test Tensile strength test: The sample size is 12cm×4cm×0.4cm. The test is carried out according to GB / T1040.1-2018 standard. The tensile properties are tested by a universal material testing machine with a tensile rate of 50mm / min.

[0042] Right-angle tear strength: tested according to QB / T1130-1991 standard; the results are shown in Table 4.

[0043] Table 4 Mechanical properties test of Examples 12, 16-27 and Comparative Example 3

[0044] Guaiacol, as a low molecular weight hindered phenol antioxidant, is easy to volatilize during processing. The use of polymerization method to prepare polyguaiacol as an antioxidant can increase the oxidation induction temperature, so that the PP decorative film can still maintain good mechanical properties at high temperatures. It can be seen from Table 4 that in Examples 12, 16-19, if the SDS content is too high, it will interfere with the normal action mechanism of the antioxidant. If the SDS content is too low, it may not be able to fully exert its solubilization and dispersion effects, and the antioxidant's ability to capture free radicals is reduced. When preparing the PP decorative film, it is unable to prevent the occurrence of free radical chain reactions, resulting in reduced mechanical properties. In Example 18, when the molar ratio of SDS to guaiacol is 1:8, the antioxidant prepared can be used in the PP decorative film to optimize its mechanical properties. In Examples 18, 20-22, too high a concentration of aqueous hydrogen peroxide solution may change the chemical structure and properties of the product, generate byproducts, and cause the performance of the antioxidant to decrease or be lost. Moreover, the activity of horseradish peroxidase as a catalyst is affected by the concentration of aqueous hydrogen peroxide solution. Too high a concentration of aqueous hydrogen peroxide solution may inhibit the activity of the enzyme and even cause the enzyme to be inactivated. In Example 20, the concentration of aqueous hydrogen peroxide solution is most suitable at 12 wt %, and the antioxidant prepared helps the material maintain structural integrity when subjected to external forces, thereby enhancing mechanical properties. In Examples 20, 23-25, if the stirring time is too short, the reactants fail to fully react, and if the stirring time is too long, the antioxidant molecules will be degraded, which will lead to a decrease in the stability of the antioxidant, thereby causing the PP decorative film to lose its mechanical strength due to thermal degradation; in Example 23, when the stirring time is 1.7h, the antioxidant obtained has the best performance, which can protect the molecular chain of the PP material from external damage, prevent it from breaking and degradation, thereby maintaining the stability of the mechanical properties of the PP decorative film, so that the PP decorative film can still maintain good mechanical properties at high temperatures. In Examples 23, 26-27, adding an appropriate amount of antioxidant can reduce thermal degradation during the melting process, reduce melt viscosity, improve fluidity, and thus improve the mechanical properties of the finished product. However, adding too much antioxidant will destroy the internal structure of the material, resulting in a decrease in mechanical properties, and too much antioxidant will destroy the thermal stability of the material, causing the material to be more susceptible to degradation, thereby affecting the mechanical properties. In Example 26, when the molar ratio of SDS to guaiacol was 1:8, the concentration of the hydrogen peroxide solution was 12wt%, and the stirring time was 1.7h, the antioxidant obtained had the best antioxidant effect. When 3 parts of the antioxidant were added to the PP decorative film, the mechanical properties were the best, with a tensile strength of 59MPa and a right-angle tear strength of 187N / mm. In Comparative Example 3, the PP decorative film obtained without the addition of an antioxidant was prone to thermal deformation, resulting in a decrease in mechanical properties, with a tensile strength of only 28MPa and a right-angle tear strength of 120N / mm.

[0045] Embodiment 29

[0046] The SDS and the guaiacol are dissolved in 45 ml of the phosphate buffer at a molar ratio of 1:8 to obtain the mixed solution 1; 0.1 mmol of the horseradish peroxidase is dissolved in 5 ml of the phosphate buffer to obtain the horseradish peroxidase solution; the horseradish peroxidase solution is dripped into the mixed solution 1 at room temperature to obtain the mixed solution 2; 1 ml of the hydrogen peroxide aqueous solution is added to the mixed solution 2, and after reacting for 20 minutes, the remaining 2 ml of the hydrogen peroxide aqueous solution is added, and the mixture is stirred for 1.7 hours, centrifuged, and filtered to obtain a filter cake; the filter cake is washed three times with the deionized water, and vacuum dried to obtain the antioxidant; the concentration of the phosphate buffer is 0.15 M; the concentration of the hydrogen peroxide aqueous solution is 12 wt%; the total amount of SDS and guaiacol added is 7 mmol Inorganic salt magnesium oxalate, sodium lignin sulfonate, dolomite and the deionized water are added into a ball mill steel tank and mixed evenly, and then ball milled at a speed of 200 r / min to obtain a reinforcing agent; the mass ratio of the sodium lignin sulfonate to the dolomite is 1:1; the ball milled particle size is 4 μm; 70 parts of PP, 1 part of nucleating agent and 8 parts of short glass fibers are added to a reactor, and stirred for 1 hour at a temperature of 170°C and a vacuum degree of 0.1 MPa to obtain a mixture one; the stirring speed is 180 r / min; 3 parts of the antioxidant polyguaiacol, 2 parts of the light stabilizer AM-101, 2 parts of the toughening agent ABS, and 8 parts of the reinforcing agent are added to the mixture one, mixed evenly at 90°C, and stirred for 1 hour to obtain a mixture two; the stirring speed is 150 r / min; the mixture two is added to a twin-screw extruder, extruded and granulated at a temperature of 180°C and a vacuum degree of 0.06 MPa to obtain a masterbatch; the masterbatch is added to a four-roll calender and calendered into a film at 190°C, and the film is cooled and rolled to obtain the composite reinforced PP decorative film; the water content of the short glass fiber is 0.07%; the diameter of the short glass fiber is 9 μm; the thickness of the film is 0.15 mm.

[0047] Examples 30-40 Referring to the preparation method and parameter conditions of Example 29, the specific differences are shown in Table 5.

[0048] Table 5 Specific preparation parameters of Examples 30-40

[0049] Example 41 Mechanical properties test Tensile strength test: The sample size is 12cm×4cm×0.4cm. The test is carried out according to GB / T1040.1-2018 standard. The tensile properties are tested by a universal material testing machine with a tensile rate of 50mm / min.

[0050] Right-angle tear strength: tested according to QB / T1130-1991 standard; the results are shown in Table 6.

[0051] Table 6 Mechanical properties test of Examples 26, 29-40

[0052] It can be seen from Table 6 that in Examples 26, 29-31, when calcium chloride is used as an inorganic salt, the mechanical properties of the obtained material are the best. The addition of calcium chloride can improve the durability of the reinforcing agent, and the addition of calcium chloride can reduce the viscosity of the reinforcing agent and improve its fluidity, which helps to better mix the components during the preparation process. In Examples 31-34, sodium lignin sulfonate has good water solubility, dispersibility and adhesion, and dolomite has excellent reinforcing and filling properties. When preparing the reinforcing agent, when the mass ratio of sodium lignin sulfonate to dolomite is 1:2, the synergistic effect of the two can be fully exerted to improve the mechanical properties and application effects of the reinforcing agent. In Examples 32, 35-38, as the ball milling speed increases, the degree of material refinement is also higher, but too high a speed may cause a significant reduction in the number of collisions between the grinding medium and the ground material, reduce the grinding efficiency, and also cause excessive refinement of the material, affecting its mechanical properties. In Example 36, when the ball milling speed is 240r / min, the components in the reinforcing agent are well dispersed, and the mechanical properties of the obtained material are the best. In Examples 36, 39-40, when the ball milling particle size is too large, stress concentration points will be generated in the matrix, causing the material to be easily damaged at the stress concentration points when subjected to force, and the mechanical properties will be reduced; moderate ball milling particle size can reduce the degree of stress concentration, improve the material's anti-destruction ability, and enable the reinforcing agent to more effectively fill the gaps in the matrix, reduce defects, and improve overall mechanical properties. In Example 36, when calcium chloride is used as an inorganic salt, the mass ratio of sodium lignin sulfonate to dolomite is 1:2, the ball milling speed is 240r / min, and the ball milling particle size is 4μm, the obtained reinforcing agent has the best effect. It is applied to PP decorative film, and the obtained PP decorative film has a tensile strength of 68MPa and a right-angle tear strength of 199N / mm, and the mechanical properties are significantly improved.

[0053] Embodiment 42

[0054] The SDS and the guaiacol are dissolved in 45 ml of the phosphate buffer at a molar ratio of 1:8 to obtain the mixed solution 1; 0.1 mmol of the horseradish peroxidase is dissolved in 5 ml of the phosphate buffer to obtain the horseradish peroxidase solution; the horseradish peroxidase solution is dripped into the mixed solution 1 at room temperature to obtain the mixed solution 2; 1 ml of the hydrogen peroxide aqueous solution is added to the mixed solution 2, and after reacting for 20 minutes, the remaining 2 ml of the hydrogen peroxide aqueous solution is added, and the mixture is stirred for 1.7 hours, centrifuged, and filtered to obtain a filter cake; the filter cake is washed three times with the deionized water, and vacuum dried to obtain the antioxidant; the concentration of the phosphate buffer is 0.15 M; the concentration of the hydrogen peroxide aqueous solution is 12 wt%; the total amount of SDS and guaiacol added is 7 mmol Inorganic salt calcium chloride, sodium lignin sulfonate, dolomite and the deionized water are added into a ball mill steel tank and mixed evenly, and then ball milled at a speed of 240 r / min to obtain a reinforcing agent; the mass ratio of the sodium lignin sulfonate to the dolomite is 1:2; the ball milled particle size is 4 μm; 70 parts of PP, 1 part of nucleating agent and 8 parts of short glass fibers are added to a reactor, and stirred for 1 hour at a temperature of 175°C and a vacuum degree of 0.1 MPa to obtain a mixture one; the stirring speed is 180 r / min; 3 parts of the antioxidant polyguaiacol, 2 parts of the light stabilizer AM-101, 2 parts of the toughening agent ABS, and 8 parts of the reinforcing agent are added to the mixture one, mixed evenly at 90°C, and stirred for 1 hour to obtain a mixture two; the stirring speed is 150 r / min; the mixture two is added to a twin-screw extruder, extruded and granulated at a temperature of 180°C and a vacuum degree of 0.06 MPa to obtain a masterbatch; the masterbatch is added to a four-roll calender and calendered into a film at 190°C, and the film is cooled and rolled to obtain the composite reinforced PP decorative film; the water content of the short glass fiber is 0.07%; the diameter of the short glass fiber is 9 μm; the thickness of the film is 0.15 mm.

[0055] Examples 43-60 Referring to the preparation method and parameter conditions of Example 42, the specific differences are shown in Table 7.

[0056] Table 7 Specific preparation parameters of Examples 43-60

[0057] Example 61 Mechanical Properties Test Tensile strength test: The sample size is 12cm×4cm×0.4cm. The test is carried out according to GB / T1040.1-2018 standard. The tensile properties are tested by a universal material testing machine with a tensile rate of 50mm / min.

[0058] Notched impact strength test: The test was conducted in accordance with GB / T1043.1-2008 standard, and the injection molded samples were measured at 23°C; the results are shown in Table 8.

[0059] Table 8 Mechanical properties test of Examples 36, 42-60

[0060] As can be seen from Table 8, in Examples 36, 42-44, by changing the reaction temperature of the mixture 1 and stirring it at 175°C, PP begins to soften and flow easily, which is conducive to the uniform dispersion of short glass fibers in the PP matrix; at the same time, high temperature can promote the function of the nucleating agent and promote the crystallization of PP, thereby enhancing the tensile strength and notched impact strength of the PP decorative film. In Examples 42, 45-47, stirring under vacuum conditions helps to remove bubbles and volatile substances in the mixture and improve the compactness of the material. When the vacuum degree is 0.3MPa, the material defects can be reduced and the mechanical properties of the material can be improved. In Examples 46, 48-54, changing the stirring time and stirring speed helps to promote the full mixing of PP and short glass fibers, reduce agglomeration, improve the uniformity and consistency of the material, and thus enhance the overall mechanical properties. In Examples 53, 55-56, mixing antioxidants, light stabilizers, toughening agents and reinforcing agents at a lower temperature to obtain mixture 2 can avoid the decomposition or failure of functional additives at high temperatures, ensure the effectiveness and stability of functional additives, and improve the mechanical properties of the material. In Examples 55, 57-60, changing the stirring time and stirring speed of the second mixture helps to evenly distribute the functional additives in the mixture, avoid excessively high or low local concentrations, and affect the material properties. When the stirring time is 1.4h and the stirring speed is 170r / min, the tensile strength and notched impact strength of the material are significantly improved. In Example 59, the reaction temperature of the first mixture is 175°C, the vacuum degree is 0.3MPa, the stirring time is 1.6h, and the stirring speed is 220r / min; the reaction temperature of the second mixture is 95°C, the stirring time is 1.4h, and the stirring speed is 170r / min. The mechanical properties of the prepared PP decorative film are the best, with a tensile strength of 87MPa and a notched impact strength of 14.6MPa.

[0061] Examples 62-72 The composite reinforced PP decorative film was prepared by referring to the preparation method and parameter conditions of Example 59, and the specific differences are shown in Table 9.

[0062] Table 9 Specific preparation parameters of Examples 62-72

[0063] Example 73 Mechanical properties test Notched impact strength test: Tested in accordance with GB / T1043.1-2008 standard, measuring injection molded samples at 23°C.

[0064] Elongation at break test: Test the elongation at break of the material according to ISO 527, the test speed is 50mm / min; the results are shown in Table 10 and Figure 1 shown.

[0065] Table 10 Mechanical properties test of Examples 59, 62-72

[0066] From Table 10 and Figure 1 It can be seen that in Examples 59, 62-63, too high a granulation temperature will cause the molecular chain structure of the material to break, the degradation rate will be accelerated, and the mechanical properties will be reduced; if the granulation temperature is too low, the material cannot be fully melted, resulting in loose bonding between particles, affecting subsequent processing and the mechanical properties of the final product. In Example 62, the granulation temperature is most suitable at 200°C. In Examples 62, 64-66, too low a vacuum degree will cause bubbles to remain during the extrusion process, affecting the density and mechanical properties of the material; when the vacuum degree is 0.08MPa, the material density is the best, and as the vacuum degree is further increased, the mechanical properties of the material decrease. In Examples 64, 67-69, too high a calendering temperature will cause the material to soften excessively, reduce its strength, and adhesion or deformation will occur on the surface of the film, affecting the mechanical properties; if the calendering temperature is too low, the material cannot be fully extended, resulting in uneven film thickness and decreased mechanical properties. In Example 68, when the calendering temperature is 220°C, the mechanical properties of the material are the best. In Examples 68, 70-72, when the film thickness is too high, the flexibility of the film is reduced, and the thicker film layer is more likely to break when subjected to external force; when the film thickness is too low, the film is too fragile and cannot withstand sufficient impact strength, resulting in reduced mechanical properties. In Example 70, when the granulation temperature is 200°C, the granulation vacuum is 0.08MPa, the calendering temperature is 220°C, and the film thickness is 0.22μm, the mechanical properties of the composite reinforced PP decorative film are the best, the notched impact strength reaches 16.2MPa, the elongation at break reaches 360%, and it is not easy to break when subjected to external force.

[0067] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A process for preparing a composite reinforced PP decorative film, characterized in that: The composite reinforced PP decorative film is prepared by the following steps: Sodium dodecyl sulfate and guaiacol are dissolved in a phosphate buffer at a molar ratio of 1:5-10 to obtain a mixed solution 1; horseradish peroxidase solution is dripped into the mixed solution 1 at room temperature to obtain a mixed solution 2; 10-15wt% aqueous hydrogen peroxide solution is added to the mixed solution 2, and the mixture is stirred for 1.5-2h, centrifuged, and filtered to obtain a filter cake; the filter cake is washed with deionized water and dried to obtain polyguaiacol as an antioxidant; Add inorganic salt, sodium lignin sulfonate, dolomite and the deionized water into a ball mill steel tank, mix them evenly, and then ball mill them at a speed of 200-300 r / min to obtain a reinforcing agent; 70 parts of PP, 0.5-1.5 parts of nucleating agent and 5-10 parts of short glass fiber are added to a reactor, stirred for 1-2 hours at a temperature of 170-180°C and a vacuum degree of 0.1-0.5MPa to obtain a mixture one; the stirring speed is 180-250r / min; 2-4 parts of the antioxidant, 2 parts of the light stabilizer, 2 parts of the toughening agent, and 8 parts of the reinforcing agent are added to the mixture one, mixed evenly at 90-100°C, and stirred for 1-2 hours to obtain a mixture two; the stirring speed is 150-200r / min; the mixture two is added to a twin-screw extruder, extruded and granulated at a temperature of 180-220°C and a vacuum degree of 0.06-0.12MPa to obtain a masterbatch; the masterbatch is added to a four-roll calender and calendered into a film at 190-250°C, and the film is cooled and rolled to obtain the composite reinforced PP decorative film.

2. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The preparation steps of the antioxidant are as follows: dissolving the sodium dodecyl sulfate and the guaiacol in the phosphate buffer to obtain the mixed solution one; dissolving the horseradish peroxidase in the phosphate buffer to obtain the horseradish peroxidase solution; dripping the horseradish peroxidase solution into the mixed solution one at room temperature to obtain the mixed solution two; adding 1 / 3 of the hydrogen peroxide aqueous solution to the mixed solution two, reacting for 20 minutes, adding the remaining 2 / 3 of the hydrogen peroxide aqueous solution, stirring for 1.5-2 hours, centrifuging, filtering to obtain the filter cake; washing the filter cake with the deionized water three times, and vacuum drying to obtain the polyguaiacol as the antioxidant; the concentration of the phosphate buffer is 0.15M.

3. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The inorganic salt is one of magnesium sulfate, magnesium oxalate, potassium chloride and calcium chloride.

4. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The ball milling particle size is 4-8 μm.

5. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The nucleating agent is WBG-Ⅱ; the toughening agent is ABS; and the light stabilizer is AM-101.

6. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The film thickness is 0.15-0.35 mm.

7. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The mass ratio of the sodium lignin sulfonate to the dolomite is 1:1-4.

8. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The moisture content of the short glass fibers is 0.05%-0.15%.

9. The process for preparing a composite reinforced PP decorative film according to claim 1, characterized in that: The short glass fibers have a diameter of 9-13 μm.

10. A composite reinforced PP decorative film, characterized in that: The raw materials for producing the composite reinforced PP decorative film include PP, a nucleating agent, short glass fibers, an antioxidant, a light stabilizer, a toughening agent, and a reinforcing agent; the composite reinforced PP decorative film is prepared by the preparation process described in any one of claims 1 to 9; by controlling the water content of the short glass fibers, the diameter of the short glass fibers, the amount of the nucleating agent, and the amount of the short glass fibers, the composite reinforced PP decorative film has a tensile strength of 46 MPa, a notched impact strength of 10.5 MPa, and an elongation at break of 328%; by preparing polyguaiacol as an antioxidant, controlling the molar ratio of sodium dodecyl sulfate and guaiacol, the concentration of the hydrogen peroxide aqueous solution, and the stirring time, the composite reinforced PP decorative film has a tensile strength of 59 MPa, and the right-angle tear strength is 187N / mm; by preparing a reinforcing agent, controlling the type of inorganic salt, the mass ratio of sodium lignin sulfonate and dolomite, the ball milling speed, and the ball milling particle size, the obtained composite reinforced PP decorative film has a tensile strength of 68MPa and a right-angle tear strength of 199N / mm; by respectively controlling the temperature, stirring time, stirring speed of mixture one and mixture two and the vacuum degree of mixture one, the obtained composite reinforced PP decorative film has a tensile strength of 87MPa and a notched impact strength of 14.6MPa; by controlling the granulation temperature, vacuum degree, calendering time, and calendering film thickness, the obtained composite reinforced PP decorative film has a notched impact strength of 16.2MPa and an elongation at break of 360%.

Citation Information

Patent Citations

  • Composite reinforced PP decorative film and preparation method thereof

    CN115838512A

  • Yellowing-resistant PP decorative film and preparation method thereof

    CN116041844A

  • Method for detecting melamine in milk powder in high sensitivity

    CN101520431A

  • Enzyme-colorimetric method for detecting residual hydrogen peroxide in foods

    CN103091312A

  • High-temperature resistant and photoaging resistant PP film and preparation method thereof

    CN104292651A